Besedno in telesno nasilje oskrbovancev nad negovalnim osebjem v Domu upokojencev in oskrbovancev Impoljca v Sevnici - Koprivnik, Natalija (Obzornik zdravstvene nege, 2002)
On the basis of a questionnaire, the author describes exposure of nursing staff to verbal and physical violence of institutionalised inmates, prevalenceof different forms, places, time periods and frequency. The second part of the article presents forms of verbal and physical violence, which inmates are most prone to use it and reactions of the staff. Satisfaction at work place is also described.
Keywords: Aged; Aggression; aggressiveness; Agresivnost; ankete; Domovi za ostarele; domovi za stare ljudi; Geriatric Nursing; Geriatrična nega; geriatrija; Homes For The Aged; nasilje; nega; Occupational Exposure; Ostareli; Poklicna izpostavljenost; Questionnaires; zdravstveni delavci